Accreting, highly magnetized neutron stars at the Eddington limit: a study of the 2016 outburst of SMC X-3 - Koliopanos, Filippos; Vasilopoulos, Georgios (2018)
Aims: We study the temporal and spectral characteristics of SMC X-3 during its recent (2016) outburst to probe accretion onto highly magnetized neutron stars (NSs) at the Eddington limit. Methods: We obtained XMM-Newton observations of SMC X-3 and combined them with long-term observations by Swift. We performed a detailed analysis of the temporal and spectral behavior of the source, as well as its short- and long-term evolution. We have also constructed a simple toy-model (based on robust theoretical predictions) in order to gain insight into the complex emission pattern of SMC X-3. Results: We confirm the pulse period of the system that has been derived by previous works and note that the pulse has a complex three-peak shape. We find that the pulsed emission is dominated by hard photons, while at energies below ~1 keV, the emission does not pulsate. We furthermore find that the shape of the pulse profile and the short- and long-term evolution of the source light-curve can be explained by invoking a combination of a "fan" and a "polar" beam. The results of our temporal study are supported by our spectroscopic analysis, which reveals a two-component emission, comprised of a hard power law and a soft thermal component. We find that the latter produces the bulk of the non-pulsating emission and is most likely the result of reprocessing the primary hard emission by optically thick material that partly obscures the central source. We also detect strong emission lines from highly ionized metals. The strength of the emission lines strongly depends on the phase. Conclusions: Our findings are in agreement with previous works. The energy and temporal evolution as well as the shape of the pulse profile and the long-term spectra evolution of the source are consistent with the expected emission pattern of the accretion column in the super-critical regime, while the large reprocessing region is consistent with the analysis of previously studied X-ray pulsars observed at high accretion rates. This reprocessing region is consistent with recently proposed theoretical and observational works that suggested that highly magnetized NSs occupy a considerable fraction of ultraluminous X-ray sources.
Keywords: Accretion; Accretion Disks; Astrophysics - High Energy Astrophysical Phenomena; Be; line: identification; magnetic fields; radiation mechanisms: general; stars: emission-line; X-rays: binaries